Amanita hiltonii (Amanitaceae), a common but frequently misidentified mushroom in southwestern Australia, and a reconsideration of A. albifimbriata and A. brunneibulbosa. - Davison, Elaine; Giustiniano, Danielle (2020)
Amanita hiltonii D.A.Reid is a common white mushroom in forested areas of southwestern Western Australia. It has been frequently misidentified as A. ananiceps (Berk.) Sacc. or A. preissii (Fr.) Sacc. Its distinguishing characters include its large size, conspicuous appendiculate cap margin, cream coloured gills, strong, unpleasant smell, amyloid, ellipsoid to elongate spores, and abundant clamp connections. Genetic sequences show collections form a well-supported clade in subgen. Amanitina (E.-J.Gilbert) E.-J. Gilbert sect. Roanokenses Singer ex Singer. Amanita albifimbriata O.K.Mill. is similar in appearance and microanatomy to A. hiltonii and these two species are synonymised. Amanita brunneibulbosa O.K.Mill. does not differ significantly from A. kalamundae O.K.Mill. and has been synonymised with it.